High-Resolution Time-Frequency Methods' Performance Analysis. (8th August 2010) - Shafi, Imran; Ahmad, Jamil; Shah, Syed Ismail; Ikram, Ataul Aziz; Ahmad Khan, Adnan; Bashir, Sajid; Kashif, Faisal Mahmood
Abstract : This work evaluates the performance of high-resolution quadratic time-frequency distributions (TFDs) including the ones obtained by the reassignment method, the optimal radially Gaussian kernel method, the t-f autoregressive moving-average spectral estimation method and the neural network-based method. The approaches are rigorously compared to each other using several objective measures. Experimental results show that the neural network-based TFDs are better in concentration and resolution performance based on various examples.